^<40>Ar-^<39>Ar Dating of Terrestrial and Exterrestrial Materials : Basalts from the Japan Sea Floor, Deccan Plateau and Meteorites from Antarctica - Kaneoka Ichiro; Takigami Yutaka (Tohoku University, 1994)
Through a series of ^<40>Ar-^<39>Ar dating for terrestrial and exterrestrial samples, the results for basalts from the Japan Sea floor, Deccan Plateau and for meteorites from Antarctica give significant information concerning their formation histories. ^<40>Ar-^<39>Ar ages of basalts from the Japan Sea floor give a constraint that the Japan Sea floor was formed at least 20 Ma. ^<40>Ar-^<39>Ar ages for dyke samples from the Deccan Plateau indicate a possibility for the occurrence of a little younger ages than that of the main plateau formations by a few million years. Meteorites collected from Antarctica show some variable ^<40>Ar-^<39>Ar ages reflecting their different thermal histories.